Moslims in Nederland: reacties op discriminatie? - Maliepaard, Mieke; Gijsberts, Mérove (Religie & Samenleving, 2015)
On the basis of nationally representative survey data collected among Muslim minorities from five different ethnic groups living in the Netherlands, this study (a) describes the extent to which Dutch Muslims experience discrimination, and (b) tests to what extent these experiences are related to increased religious identification and practice. The results indicate that particularly the larger and more established groups report relatively high levels of discrimination. The relation between discrimination and religious identification and practice which we expected on the basis of theories on reactive religiosity differs across groups and surveys: there is some evidence for reactive religiosity, but not in all ethnic groups. Importantly, discrimination never diminishes religious identification or practice. Implications are discussed.